PRELIMINARY PHYTOCHEMICAL, ANTIOXIDANT AND ANTIMICROBIAL STUDIES OF FLACOURTIA JANGOMAS FRUITS - Das, Sumit; Dewan, Nuruzzaman; Das, Kapil Joyti; Kalita, Dhritishmita (International Journal of Current Pharmaceutical Research, 2017)
Objective: To determine phytochemical, antimicrobial and in vitro antioxidant activity of Flacourtia jangomas (Family: Flacourtiaceae) Methods: The fruit extracts of the plant was taken for the phytochemical screening to identify the phytochemicals present in it. The extracts of the fruits were evaluated for antimicrobial activity against S. aureus and Escherichia coli by disc diffusion method. In vitro, antioxidant activity was performed by reducing power method, TBA method. Results: The n-butanol extracts showed significant antimicrobial activity against all the strains as compared to the standard drug. The extracts also showed antioxidant activity against the standard ascorbic acid. Conclusion: The extracts showed a high amount of antimicrobial activity and antioxidant activity.